Europe and Central Asia's Great Post-communist Social Health Insurance Experiment : Aggregate Impacts on Health Sector Outcomes - Wagstaff, Adam (2012)
The post-Communist transition to social health insurance in many of the Central and Eastern European and Central Asian countries provides a unique opportunity to try to answer some of the unresolved issues in the debate over the relative merits of social health insurance and tax-financed health systems. This paper employs regression-based generalizations of the difference-in-differences method on panel data from 28 countries for the period 1990-2004. We find that, controlling for any concurrent provider payment reforms, adoption of social health insurance increased national health spending and hospital activity rates, but did not lead to better health outcomes.